2007
DOI: 10.1089/aid.2006.0193
|View full text |Cite
|
Sign up to set email alerts
|

No Observable Correlation between Central Nervous System Side Effects and EFV Plasma Concentrations in Japanese HIV Type 1-Infected Patients Treated with EFV Containing HAART

Abstract: The present study assessed the relationship between central nervous system (CNS) side effects and plasma concentrations of efavirenz (EFV) in Japanese HIV-1-infected patients. Subjects consisted of 69 HIV-1-infected patients (57 therapy-naive and 12 therapy-experienced patients) being treated using EFV in combination with other antiretroviral agents at the outpatient HIV clinic. Successful virological treatment was achieved in 61 patients. Eight patients discontinued EFV containing therapy because CNS symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…Some investigators have found positive relations [15,17,18], whereas others have not [19,20]. This difference may be method-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have found positive relations [15,17,18], whereas others have not [19,20]. This difference may be method-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…One factor attributing to this individual variation in levels is polymorphism of the CYP2B6 enzyme on cytochrome P450, as EFV is a substrate of this enzyme. [9] The prevalence of the slow-metabolising genotype was 30% in a Botswana study, and other studies have also shown a relatively higher incidence of this genotype in African populations. [14] …”
Section: Discussionmentioning
confidence: 79%
“…[7] CNS symptoms are the most frequently reported side-effects in HIVpositive patients on EFV, and include dizziness, headache, confusion, stupor, impaired concentration, agitation, amnesia, depersonalisation, hallucinations, insomnia and strange dreams. [6,[8][9][10][11][12][13][14] The frequency of CNS side-effects is estimated to be 20 -40%. [10] The majority of patients who develop CNS and psychiatric adverse effects do so in the first 6 weeks of treatment, [11] with most symptoms resolving by 6 -10 weeks after treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CNS adverse effects are associated with the higher levels of EFV in plasma [38][39][40], while others failed to demonsrate the association [41,42]. Two studies have demonstrated the association between the CYP2B6 genotype and the incidence of CNS adverse effects [14,15].…”
Section: Cyp2b6 Genotype and Adverse Effects Associated With Nnrti Usementioning
confidence: 99%